The meaning of words in the preservation mayor of Al-Samin Al-Halabi (d. 756 AH)) (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon our Prophet Muhammad and his family and companions.Umdat al-Hafiz fi Tafsir Ashraf al-Alfaz, a linguistic dictionary of the words of the Holy Qur’an; For Sheikh Ahmed binYusuf bin Abd Al-Daem, known as Al-Samin Al-Halabi (d. 756 AH); Arranged by its author according to the letters of the dictionaryRelying on the origins of the word without its additions, and he mentioned in each of the words a linguistic analysis citingVerses from the Holy Qur’an at times, and the hadith of the Prophet, poetry and Arabic proverbs at other timesHe cited the sayings of the language owners to support the validity of the words he is looking for.Al-Sameen Al-Halabi interpreted the semantics of the words in several ways, including: Direct InterpretationThe most common methods of interpreting words among the old and modern lexicographers, and they are meant to be interpretedsemantic positivist lexical. Interpretation in context, as it is one of the methods of interpretation of Quranic words. becauseThe context is the first determinant of the meaning of that word in the place in which it became hungry.The causal context is another way of interpreting the words of the fat person. Because it includes what was stated inThe lexicon is an explanation for the use of the linguistic formula, so we find the contextual context a lamp that leads to knowing thatThe meaning of this word.And the investigator of the dictionary has extracted his hadiths; Attributing the honorable hadiths to their reference; And the verses to QalihaAnd provided the dictionary with scientific indexes